Pemasangan Mikrofon untuk Instrumen Rebab pada Gamelan Wayang - Wasono, Adi (Institut Seni Indonesia Surakarta, 2023)
Article with the title “ Pemasangan Mikrofon untuk Instrumen Rebab Pada Gamelan Wayang (Installation of Microphones for Rebab Instruments in Gamelan Wayang)” are various possibilities that can be applied in selecting the type of microphone and its placement on the ricikan rebab (rebab string) so that it can be used as an alternative in installing it. Installing microphones is part of the sound system work. Considerations for sound system work are usually based on room conditions, number of spectators and noise levels. Sound system devices are used to convey the sound of instruments to the musicians, to the audience, and to the performers on stage (dance, dhalang, theater). The amplification of all instruments and the human voice is the overall reference. A harmonious musical connection of course requires a quality sound system. One instrument that really needs attention is rebab. Musically, the rebab has a very important role in wayang performances, namely as a pamurba for songs. The source of the sound comes from the strings that are rubbed with a bow with an acoustic chamber in the form of wood which is made concave and covered with thin skin and a string is attached as an intermediary between the strings and the skin. The condition of this rebab organ gives it its own character. The frequency produced by the rebab sound is approximately 160 Hz and above. The microphone installation that is often used is the dynamic Shure SM57 type, and other types of microphones that have been used are the AKG C535, AKG SE-391B with condenser type. As technology develops, new microphone products are discovered that are more suited to the needs of rebab sound amplification. Explorations have been carried out so that several types and brands of microphones can be considered for use on rebab instruments.